Pengaruh Kohesivitas terhadap Kinerja Tim pada Anggota Organisasi Himpunan Mahasiswa Jurusan Psikologi UIN Walisongo Semarang - Jauza Nabila Azzah; Tegar Valentino; Alvina Rahmawati; Merlina Eramawati; Siti Hikmah (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study aims to determine the effect of cohesiveness on team performance among members of the Psychology Student Association at UIN Walisongo Semarang. The background of this study is based on the fact that the dynamics of cooperation and cohesiveness are very important in determining team effectiveness, especially in student organizations that have fluctuating membership and commitment. This study was conducted quantitatively using cohesiveness and team performance scales and analyzed using normality tests, Pearson's correlation, and simple linear regression. The results showed that both variables were normally distributed, with very low correlation values and significance values above 0.05. The regression results also showed that cohesiveness only explained a small portion of the variation in team performance, indicating that other factors were more dominant in influencing the performance of organization members. This conclusion suggests that improving team performance in student organizations cannot rely solely on cohesiveness, but must also consider other aspects such as individual motivation, role clarity, effective communication, and individual commitment.